Immunity against vaccine-preventable diseases among pregnant employees in Germany. A situation analysis before the introduction of the Measles Protection Act - Wolfschmidt-Fietkau, Anna; Goertz, Ruediger S.; Goertzen, Stephanie; Schmid, Klaus; Seidling, Marie; Gherman, Elsa; Ochmann, Uta; Drexler, Hans (Vaccine, 2024)
Background: Immunization against vaccine-preventable diseases prior to pregnancy is an important measure of primary prevention both for the mother and the unborn child. We analyzed immunity rates against measles, mumps, rubella, varicella, and pertussis in pregnant employees in Germany prior to significant changes in legal conditions in 2020, to provide a basis of comparison for future research. Methods: We analyzed occupational-medical routine data in three collectives of pregnant women with an occupational risk of infection in the years 2018 and 2019: 1: hospital staff with regular access to an in-house company physician (n = 148); 2: employees in childcare with regular access to external occupational-health services (n = 139); 3: teachers with no regular access to occupational healthcare (n = 285). Immune status was assessed by a physician based on vaccination certificates, laboratory results, and medical documentation on prior infections. We compared immunity rates against measles, rubella, varicella, and pertussis as well as full immunity against all targeted vaccine-preventable diseases. Results: Altogether, n = 572 pregnant women were included in our study. Of these women, 96.5 % were immune to rubella, 95.8 % to varicella, 88.3 % to measles, 82.7 % to mumps, and 67.8 % to pertussis. Only 56.2 % of the women had full immunity against all targeted vaccine-preventable diseases. Collective 1 showed the highest immunity rates against measles and pertussis as well as the highest rate of full immunity against all targeted vaccine-preventable diseases. The immunity rates against rubella and varicella did not differ significantly between the collectives. With the exception of rubella, the lowest immunity rates during pregnancy were found in Collective 3. Conclusion: We found pregnancy-relevant immunity gaps in all our study groups with significant differences between the collectives. Considering the potentially devastating consequences of infections during pregnancy, all medical professionals and health-policy makers should be involved in an increased effort to improve vaccination rates prior to pregnancy.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Immunity; Infection prevention; Occupational medicine; Pregnancy; Vaccination